Implementation of government regulations and, regulation the minister of finance in income tax withholding 2024 - Maulana, Ayang Fristia; Adawiyah, Robiatul; Suhartini, Sulis; Abdurrohman, Muhammad (Journal of Law Science, 2024)
Income generated by individuals or companies in the form of salaries, business profits, gifts and honorariums or other income whether from within the country or abroad, there are provisions for the collection of Income Tax carried out by the government. In 2024, the government will promulgate changes to the calculation scheme related to Income Tax 21, which aims to facilitate the calculation process of withholding Income Tax Article 21. However, according to employees, especially permanent employees, the Income Tax Article 21 calculation scheme that was recently approved by the government has made employees uneasy. Because the new Income Tax withholding scheme makes employees' salaries deducted high tax costs due to the tax withholding calculation scheme using the TER rate and the use of the old rate is only used at the end of the tax year